Extraction of Reliable Molecular Information from Diffusion NMR Spectroscopy: Hydrodynamic Volume or Molecular Mass?. Issue 42 (3rd July 2019) - Zaccaria, Francesco; Zuccaccia, Cristiano; Cipullo, Roberta; Macchioni, Alceo
Abstract: Measuring accurate translational self‐diffusion coefficients ( D t ) by NMR techniques with modern spectrometers has become rather routine. In contrast, the derivation of reliable molecular information therefrom still remains a nontrivial task. In this paper, two established approaches to estimating molecular size in terms of hydrodynamic volume ( V H ) or molecular weight (M) are compared. Ad hoc designed experiments allowed the critical aspects of their application to be explored by translating relatively complex theoretical principles into practical take‐home messages. For instance, comparing the D t values of three isosteric Cp2 MCl2 complexes (Cp=cyclopentadienyl, M=Ti, Zr, Hf), having significantly different molecular mass, provided an empirical demonstration that V H is the critical molecular property affecting D t . This central concept served to clarify the assumptions behind the derivation of D t =ƒ(M) power laws from the Stokes–Einstein equation. Some pitfalls in establishing log ( D t ) versus log (M) linear correlations for a set of species have been highlighted by further investigations of selected examples. The effectiveness of the Stokes–Einstein equation itself in describing the aggregation or polymerization of differently shaped species has been explored by comparing, for example, a ball‐shaped silsesquioxane cage with its cigar‐like dimeric form, or styrene with polystyrene macromolecules. Abstract : Diffusion NMR techniques can be used to determine the size of molecules in solution (see figure). Selected examples have allowed the basic principles underlying translational self‐diffusion to be recalled and to derive practical lessons for the accurate manipulation of self‐diffusion coefficients ( D t ).